4
$\begingroup$

In the paper linear forms in the logarithms of real algebraic numbers close to 1, it is written on page 5 that-

$y \geq (b+1)$ since, $(b+1)b^n < (b+1)^n b$ and it was given that $(b+1)x^n - by^n =1$.

but $(b+1)x^n - by^n =1 \implies (b+1)x^n > by^n $, and together with $(b+1)b^n < (b+1)^n b$, I don't see how we reach at $y \geq (b+1)$

Please explain, Thanks in advance.

$\endgroup$
3
$\begingroup$

The context is that $b, x, y, n$ are positive integers here, and $(x, y) \neq (1, 1)$.

Under these conditions, $x < y$ must hold (neither $x = y$ nor $x > y$ can), thus $y \geqslant x + 1$, and therefore $(b + 1)x^n - b(x + 1)^n \geqslant 1$. So this is $> 0$, i.e. $$\frac{b + 1}{b} > \Big(\frac{x + 1}{x}\Big)^n \geqslant \frac{x + 1}{x}$$ (and this even implies that $x > b$, i.e. $y > b + 1$).

$\endgroup$
1
$\begingroup$

The given equation is-

$(b+1)x^n - by^n =1 \cdots (1)$.

Case $1$: If $x=y$,

then equation (1) becomes $(b+1)x^n - bx^n =1 \implies bx^n+x^n - bx^n =1 \implies x^n =1 \implies x=1 $, but it is given that $(x, y) \neq (1, 1)$. So, $x \neq y$.

Case $2$: If $x>y$,

then, let $x=y+c$ (where $c>0$, $c$ is an integer since x,y are integers) we substitute the value of $x$ in equation (1) -

$(b+1)(y+c)^n - by^n =1\implies b(y+c)^n+(y+c)^n - by^n =1 $. By inspection, we find that the difference between $b(y+c)^n+(y+c)^n $ and $by^n$ is larger than $1$ (reader will see it more clearly if he expands $(y+c)^n $ (binomial expansion), note that $c$ is an integer).

Case $3$: So, $x<y$ (the only possibility). Let, $y=x+d$. Then equation (1) becomes-

$(b+1)x^n - b(x+d)^n =1 $ [substituting the value of $y=x+d$ in $(1)$]

$\implies \frac{b+1}{b} - (\frac{x+d}{x})^n =\frac{1}{bx^n} $ [dividing both sides of the equitation by $bx^n$ ]

$\implies \frac{b+1}{b} - (\frac{x+d}{x})^n >0 $ [Since, $\frac{1}{bx^n}>0$]

$\implies \frac{b+1}{b} > (\frac{x+d}{x})^n $ $\implies \frac{b+1}{b} > \frac{x+d}{x}$ [Since, $(\frac{x+d}{x})^n > (\frac{x+d}{x}) $ ] $\implies 1+ \frac{1}{b} > 1 + \frac{d}{x} $ $\implies \frac{1}{b} >\frac{d}{x} $ $\implies x > bd $. Here, $d \geq 1$, we see that for $d=1, x>b$, as we have found earlier $y>x$, we deduce, $y>b \implies y\geq b+1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.